PENGARUH PENGGUNAAN LAHAN DAN KEMIRINGAN LERENG TERHADAP SIFAT FISIK TANAH DI KECAMATAN KURUN KABUPATEN GUNUNG MAS - Soaloon Sinaga; Vera Amelia; Rayane D Batubara (Agrienvi: Jurnal Ilmu Pertanian, 2020)
Changes in land use are one of the factors that affect the decline in soil physical properties. The occurs due to differences in vegetation characteristics, canopy density, and thickness of the canopy cover. This study tries to make an effort to explore the physical nature of the soil in several land use, with different slopes of the land. The research location is in Kurun District, Gunung Mas Regency. The study started from May to November 2020. The results showed that land use affected the physical properties of the soil on the land. The physical properties of soil in forests are better than plantations that have lower levels of organic matter, higher content weight, lesser percent clay, higher percent dust which makes the soil more easily eroded. Keywords: Land use, slope, soil physical properties.